(untitled) (Journal of Hama University, 2022)
This research aimed at identifying the prevalent personality types among a sample of master’s students at Damascus University according to the nine personality types’ scale (Enneagram), and measuring the differences in these types according to variables of (gender, type of master, and type of faculty). The research sample consisted of (651) students, including (280) males, and (371) females at the master’s level of both types (academic, rehabilitation and specialty) in faculties (theoretical and applied) at the University of Damascus. The research followed the descriptive method, and the scale of nine personality types (Enneagram), which prepared by (Riso & Hudson, 1995) was used after checking its psychometric characteristics. The research results indicated the following: The personality type (investigator) was the dominant pattern among the members of the research sample, followed by the personality type (reformer), while the personality type (individualistic) came in the last rank.There were no statistically significant differences between the mean scores of research sample members on the scale of nine personality types (Enneagram) according to variable of (gender). There were statistically significant differences between the mean scores of research sample members on the scale of nine personality types (Enneagram) according to variable of (type of master) in favor of academic master’s students at the investigator and reformer personality types, and in favor of rehabilitation and specialty master’s students at the helper and loyalist personality types.-There were statistically significant differences between the mean scores of research sample members on the scale of nine personality types (Enneagram) according to variable of (type of faculty) in favor of theoretical faculties master’s students at the loyalist and Enthusiast personality types, and in favor of theoretical faculties master’s students at the achieve and peace maker personality types.